Strategy to Improve Teacher Performance Through Teacher Professional Education - Wahyuni, Iis; Hamid, Abdul; Ma’arif, Mohamad Ahyar (Journal of Educational Management Research, 2025)
This study aims to analyze strategies for improving teacher performance through the Teacher Professional Education Program in elementary schools. The background of this study is the importance of teacher professionalism in supporting the quality of national education. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation. The data results were analyzed using thematic analysis with the Clarke and Braun approach. The results of the study indicate that Teacher Professional Education plays a positive role in improving teacher competence, especially in managing learning, preparing teaching materials, and delivering materials effectively. In addition, there is an increase in the culture of regular training which also encourages an increase in teacher professionalism. Initial obstacles such as limited facilities and infrastructure were successfully overcome through the principal's initiative. The findings are expected to be a reference as an effective strategy in supporting the development of teacher performance in a sustainable manner in elementary schools.